Reaching adolescents with health services: Systematic development of an adolescent health check-ups and wellbeing programme in Ghana (Y-Check, Ghana) - Weobong, Benedict; Glozah, Franklin N.; Taylor-Abdulai, Hannah B.; Koka, Eric; Addae, Nancy; Alor, Stanley; Kohl, Kid; Banati, Prerna; Adongo, Philip B.; Ross, David A. (PloS one, 2024)
Routine health check-ups may improve adolescent health, but global guidelines are lacking. Phase 1 of the WHO-coordinated Y-Check Research Programme involved three African cities to co-produce a programme of adolescent health check-ups. We describe a systematic approach to developing a routine adolescent health check-ups and wellbeing programme (Y-Check) to contribute evidence on whether adolescent health check-ups should be part of routine health services in Ghana. Y-Check Phase 1 was conducted in four communities in Cape Coast Ghana, over two stages using a variety of methods: (a) needs assessment and landscape analysis on the health of adolescents (existing policies/programmes, school system, adolescent health conditions) was conducted through desk-review and interviews with key informants to identify the potential content, delivery strategy and settings for adolescent health check-ups in this context; (b) co-designing the Y-Check intervention framework through person-centred participatory workshops and a consensus-building workshop with multiple stakeholders, including adolescents (10-19 years) and their parents. The study was conducted between January 2020 and October 2020. The Y-Check intervention consists of two check-ups with content that is tailored to the needs of younger adolescents and older adolescents; delivered at both school and community settings by a team of trained staff in multiple steps involving up to four stations. Y-Check includes a referral system for adolescents with any problems that cannot be investigated or treated on-the-spot. Our systematic approach to co-producing Y-Check has resulted in an intervention whose content and structure is determined by the local context, and which was adjudged by multiple stakeholders to be likely to be both useful and acceptable, and which builds on best practice. As a logical next step, the Y-Check will be subjected to pilot testing and implementation research to rigorously evaluate the feasibility, acceptability, coverage, yield of previously undiagnosed conditions and cost of these health check-ups.